Statistics on Anisotropy of Magnetic Susceptibility Ellipsoids: a Case Study from the Tjörnes Fracture Zone - Baumgarte, Julia (Carleton Digital Commons, 2021)
Anisotropy of magnetic susceptibility (AMS) is a straightforward geophysical tool that can detect unobservable rock fabrics. Many previous studies use AMS results for examining fabric and deformation at the outcrop scale or in combination with other geological tools, commonly breaking the AMS ellipsoid into its axes to analyze separately. Because AMS data are ellipsoidal and therefore complex packages of data, it is important that they be treated with rigorous statistical methods. I use AMS data from the Tjörnes Fracture Zone in northern Iceland to test the utility of AMS as a geological tool in rocks that are regionally extensive and largely homogenous. I show that applying orientation statistics to these complex data can reveal flow direction in lavas at a regional scale and detect other spatial trends that are statistically robust.